(untitled) (Hekima Review, 2005)
In the Ancient Israel, holy war was, according to Gerhard Von Rad, understood as “an eminently cultic undertaking, that is, prescribedand sanctioned by fixed, traditional, sacred rites and observances” 1. As a cultic act of religious community, its featurewas the demand for faith in Yahweh’s saving power (the Lord said to David): “I will deliver your enemy into your grasp”(1Sam 24:5).